TOPICS AND ISSUES RAISED IN THE WORKS OF GAFUR GULYAM - Durdona Rasulmuxamedova (Scholar Express Journals, 2023)
Academician Gafur Gulyam, a great representative of Uzbek literature of the 20th century, had a unique talent. His work "Mischievous" is a unique school. This article describes the daily life of the Uzbek people at the beginning of the twentieth century, the socio-economic life of the beginning of the First World War, and also highlights the hardships of the life of ordinary people, market events, the adventures of a naughty boy, all the details of the life of people of that time. The article gives a vivid picture of how children walk and experience different adventures on their own. In other words, the writer was able to masterfully show that the boy's adventures are based on difficult living conditions.
Keywords: story; speech of heroes; market landscape; socio-economic problems